Disguise and recognition in the Odyssey - Murnaghan, Sheila, 1951- (Greek studies., 2011)
"This book is a comprehensive study of the Odyssey's plot, which shows how the motifs of disguise and recognition are used to articulate the central values of Homeric society. The story of Odysseus' homecoming is discussed in relation to family dynamics, heroic competition, the social institutions of marriage and hospitality, gender relations, and the enduring power of song."--Provided by publisher.